Greetings from Novorossiya : eyewitness to the war in Ukraine - Pieniążek, Paweł (Series in Russian and East European studies., 2017)
In autumn of 2014, the people of Ukraine rose up against their authoritarian president Yanukovych, rallying for democracy and occupying Kiev's main square under the blue flag of the European Union. They were met with bullets from the regime, and the slaughter of a hundred peaceful protesters made the Euromaidan synonymous with moral courage and the yearning for freedom. Yanukovych fled to Russia, and Putin, sensing a potentially existential threat to his own regime, struck back. Employing a noxious brew of mercenaries, propaganda, local agents of influence, fake news, and disguised Russian special forces, Putin quickly acted to split Ukraine in two. In the midst of chaos he had created, he used the opportunity to seize Crimea - the first invasion of sovereign territory by a European power since end of the Second World War. The Russians then turned their attention to building up a largely phony separatist movement in eastern Ukraine, complete with all the trappings of statehood for what they cynically called Novorossiya, New Russia , fueling a bloody civil war. More than ten thousand people, including many innocent civilians, have perished in this conflict so far, with no end in sight. Polish journalist Pawel Pieniazek was among the first to visit the war-torn region, and spent over two years there. Greetings from Novorossiya is his vivid firsthand account of the conflict. Unlike western journalists, thanks to his fluency in both Ukrainian and Russian he was able to gain access and move among all sides in the conflict. He was the first reporter to reach the scene when Russian troops in Ukraine accidentally shot down a civilian airliner, killing 298 people. With powerful color photos, telling interviews from the local population, and Pieniazek's brilliant reportage, this book documents the dramatic events as they transpired. Originally published in Polish, this unique view of history-in-the-making brings to life the tragedy of Ukraine for a western audience. Historian Timothy Snyder provides wider context in his superb introduction and explores the significance of this ongoing conflict at the border of East and West.